Positive Time and Almost Time Periodic Solutions for the Quasigeostrophic Motions - Zhan, Mei-Qin (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, we study the quasigeostrophic equation, which is a prototypical geophysical fluid model. We will show the existence of positive solutions and almost time-periodic solutions.